IFN-γ activates the tumor cell-intrinsic STING pathway through the induction of DNA damage and cytosolic dsDNA formation. (31st December 2022) - Xiong, Hui; Xi, Yu; Yuan, Zhiwei; Wang, Boyu; Hu, Shaojie; Fang, Can; Cai, Yixin; Fu, Xiangning; Li, Lequn
ABSTRACT: Stimulator of interferon genes (STING) pathway activation predicts the effectiveness of targeting the PD-1/PD-L1 axis in lung cancer. Active IFN-γ signaling is a common feature in tumors that respond to PD-1/PD-L1 blockade. The connection between IFN-γ and STING signaling in cancer cells has not been documented. We showed that IFN-γ caused DNA damage and the accumulation of cytosolic dsDNA, leading to the activation of the cGAS- and IFI16-dependent STING pathway in lung adenocarcinoma cells. IFN-γ-induced iNOS expression and nitric oxide production were responsible for DNA damage and STING activation. Additional etoposide treatment enhanced IFN-γ-induced IFN-β and CCL5 expression. Tumor-infiltrating T cells stimulated with a combination of anti-CD3 and anti-PD-1 antibodies caused STING activation and increased IFN-β and CCL5 expression in lung adenocarcinoma. These effects were abrogated by the addition of an IFN-γ neutralizing antibody. Our results suggest that the activation of tumor-infiltrating T cells could alter the tumor microenvironment via the IFN-γ-mediated activation of STING signaling in cancer cells.